2021
DOI: 10.1042/bsr20210029
|View full text |Cite
|
Sign up to set email alerts
|

Implications of ADAM17 activation for hyperglycaemia, obesity and type 2 diabetes

Abstract: In this review, we focus specifically on the role that the metalloproteinase, A Disintegrin and Metalloproteinase 17 [ADAM17] plays in the development and progression of the metabolic syndrome. There is a well-recognised link between the ADAM17 substrate tumour necrosis factor α (TNF-α) and obesity, inflammation and diabetes. In addition, knocking out ADAM17 in mice leads to an extremely lean phenotype. Importantly, ADAM17-deficient mice exhibit one of the most pronounced examples of hypermetabolism in rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 80 publications
(116 reference statements)
2
12
0
Order By: Relevance
“…Maximal ADAM1 7 expression in PBCs of COVID-19 patients with obesity (BMI > 30) is explicable, considering that obesity often associates with metabolic inflammation, with which ADAM17 activity has recognized links, through proteolytic processing of pro-TNFalfa, ACE2, IL-6R and other membrane-anchored proteins in adipose tissue and other tissues [ 45 , 46 ]. Evidence in humans and rodents indicates that aging and obesity cooperatively increase vascular endothelial ADAM17 activity and the release of soluble TNFalfa by adipose tissue cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maximal ADAM1 7 expression in PBCs of COVID-19 patients with obesity (BMI > 30) is explicable, considering that obesity often associates with metabolic inflammation, with which ADAM17 activity has recognized links, through proteolytic processing of pro-TNFalfa, ACE2, IL-6R and other membrane-anchored proteins in adipose tissue and other tissues [ 45 , 46 ]. Evidence in humans and rodents indicates that aging and obesity cooperatively increase vascular endothelial ADAM17 activity and the release of soluble TNFalfa by adipose tissue cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding would be explained by two different approaches previously proposed in the literature. One would be the influence of high blood glucose levels in inducing hyperactivation of the sympathetic nervous system and also promoting ADAM17 expression [ 18 ]. Matthews et al hypothesized that an increase in ADAM17 induces renal sympathetic nervous system activity and in turn induces SGLT2 (Sodium Glucose Cotransporter 2) expression, which promotes glucose reabsorption and hyperglycemia [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One would be the influence of high blood glucose levels in inducing hyperactivation of the sympathetic nervous system and also promoting ADAM17 expression [ 18 ]. Matthews et al hypothesized that an increase in ADAM17 induces renal sympathetic nervous system activity and in turn induces SGLT2 (Sodium Glucose Cotransporter 2) expression, which promotes glucose reabsorption and hyperglycemia [ 18 ]. In this line, our study demonstrated that Adam17 deletion on proximal tubular cells prevents increased blood glucose levels and glucose intolerance to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Furthermore, evidence is provided that ADAM-17 plays a role in metabolic syndrome-related pathologies. 50 , 51 On the other hand, some clear data also show the possible relationship between the presence of metabolic syndrome and the severity of COVID-19. 52 Accordingly, several of the features of the metabolic syndrome seem to be associated with a worse prognosis in patients with COVID-19.…”
Section: Risk Factors For Covid-19 and Defective Efferocytosismentioning
confidence: 99%